Fabrication and formation mechanism of poly (L-lactic acid) ultrafine multi-porous hollow fiber by electrospinning - Q. Z. Yu; Y. M. Qin (eXPRESS Polymer Letters)
Poly(L-lactic acid) (PLLA) ultrafine multi-porous hollow fibers are fabricated by electrospinning with methylene dichloride as solvent. The Kirkendall effect has been widely applied for the fabrication of hollow structure in metals and inorganic materials. In this study, a conceptual extension is proposed for the formation mechanism: the development of porous hollow fiber undergoes three stages. The initial stage is the generation of small voids or pits on the surface of the fiber via surface diffusion and phase separation; the second stage is the formation of multi-pores penetrating the core of the fiber through the interaction of Kirkendall effect, surface diffusion and phase separation; the third stage is dominated by surface diffusion of the core material along the pore surface. To explore the formation conditions, the factors including ambient temperature, relativity humidity (R. H.), molecular weight and fiber diameter are studied. The longitudinal and cross sectional morphologies of these fibers are examined by scanning electron micrograph (SEM). The results show that the prerequisite for the formation of uniform porous hollow PLLA fibers include moderate ambient temperature (10~20°C) and appropriate molecular weight for the PLLA, as well as the diameter of the fiber in the range of several micrometers to about 100 nanometers.